2010
DOI: 10.5336/medsci.2010-18178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Tissue on Vibration-Induced Electrical Activity of Muscles

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The effect of muscle activity on bone tissue is well documented. However, there is not enough data on effect of bone tissue on muscle activity. The aim of this study was to determine whether bone exposed to cyclic mechanical loading affects muscle electrical activity in healthy adult volunteers. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Fifty-six volunteers were included in this study. Muscle electrical activity was measured on flexor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…BMR activates the muscles that could eliminate such asymmetrical loading. As a result, optimal distribution of the mechanical load through the bone is provided (11,15,16).…”
Section: Possible Mechanisms Underlying Vibration-induced Reflex Muscmentioning
confidence: 99%
See 2 more Smart Citations
“…BMR activates the muscles that could eliminate such asymmetrical loading. As a result, optimal distribution of the mechanical load through the bone is provided (11,15,16).…”
Section: Possible Mechanisms Underlying Vibration-induced Reflex Muscmentioning
confidence: 99%
“…There, they activate motoneurons that cause the muscle to contract (2,3,6,7). However, it has been reported that the sensitivity of the muscle spindle decreases or does not increase, and that presynaptic inhibition occurs in Group Ia afferent fibres with vibration (6,(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 The bone has been reported to have a potential effect on the ipsilateral muscle activity. 12,13 However, whether the bone has any effect on the contralateral homologous muscle activity is not known. This study investigated whether the bone mineral density (BMD) or bone mineral content (BMC) of the distal radius had any effect on the resting muscle activity of the contralateral wrist flexor muscles during unilateral forearm vibration in healthy adults.…”
mentioning
confidence: 99%
“…Through the bone myoregulation reflex, bone is sensitive to mechanical stimuli and can send mechanical input signals to central nervous system, resulting in neuronal stimulation of muscle activity. 12,13 The vibration can increase the strength of the contralateral and ipsilateral muscles.…”
mentioning
confidence: 99%